ALTERNATIVES OF DOMESTIC WASTEWATER SLUDGE DRYING PROCESSES FOR ENERGY RECOVERY : A REVIEW - Camera, S.; Pineda-Vásquez, T.; Bianchi, F. M.; Martins, L. S.; Virmond, E.; Watzko, E. S. (Revista de Engenharia Térmica, 2021)
As communities grow, cities need to increase their capacity to collect and treat domestic wastewater. The need of larger domestic wastewater treatment plants and proper disposal of its solid waste has attracted the scientific community to research about new technologies that will use those systems and waste as a way to generate energy. The moisture content of a fuel effects the combustion products and the energy released by the reaction. Therefore, in order to make biomass to be a viable fuel option, the technological and scientific challenges of the drying process of wastewater sludge must be faced and overcome so the lowest moisture content level is achieved. Conventional drying processes as for example, direct and indirect thermal drying, are commonly used. However, other processes using renewable energy as for example solar drying are also being studied by the scientist around the world. Moisture content, physical-chemical properties as for example, heating values, composition, ash fusibility are all relevant properties taken into consideration when choosing a fuel for a specific application. The herein review is intended to present some existing domestic wastewater drying processes, alternative ways of improving the efficiency of those processes.